Ultrasound-guided serratus anterior plane block to prevent neurocognitive impairment in elderly patients after thoracoscopic lobectomy: protocol for a single-centre, double-blind, randomised controlled trial - Wei Wu; Di Feng; Huan Xu; Hong Shi; Dan-Yang Wang; Mei-Yun Liu (BMJ Open)
Introduction Postoperative neurocognitive dysfunction (PND), including postoperative delirium (POD), is a common complication in elderly patients after major surgeries, often leading to poor postoperative recovery. Although the pathological mechanism underlying PND is still unclear, postoperative pain is strongly associated with the development of PND. The ultrasound-guided serratus anterior plane block (SAPB) has been reported to relieve postoperative pain in thoracic surgery. Therefore, this prospective trial hypothesises that SAPB may reduce the incidence of PND in the elderly undergoing thoracoscopic lobectomy.Methods and analysis This study is designed as a single-centre, double-blind, randomised controlled clinical trial. A total of 256 elderly patients scheduled to undergo thoracoscopic lobectomy at Shanghai Pulmonary Hospital will be randomly assigned to general anaesthesia group or SAPB group. The primary outcome is the incidence of PND 7 days postoperatively or before discharge from hospital. The secondary outcomes include the occurrence of POD, the postoperative pain scores, Quality of Recovery at 1–2 days postoperatively and incidence of PND at 3 months postoperatively. The levels of fasting blood glucose in peripheral blood will be examined before and 1–2 days postoperatively.Ethics and dissemination The trial has been approved by the Clinical Research Ethics Committee of Shanghai Pulmonary Hospital (identifier: K20-290). All participants will be required to provide written informed consent before any protocol-specific procedures. Findings will be disseminated in a peer-reviewed journal and in national and/or international meetings to guide future practice.Trial registration number ChiCTR2100052633.